2014
DOI: 10.1007/s12032-014-0161-y
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of HuR expression in human malignancy

Abstract: Hu-antigen R (HuR) is an RNA-binding protein that regulates the stability, translation, and nucleus-to-cytoplasm translocation of target mRNAs. The aim of the present review was to summarize and present the currently available information in the English literature on HuR expression in various human tumors, verifying its possible clinical significance. HuR function is directly linked to its subcellular localization. In normal cells, HuR is mostly localized in the nucleus, while in malignant cells, an increase i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
70
3
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 71 publications
(80 citation statements)
references
References 125 publications
3
70
3
4
Order By: Relevance
“…ER-targeted endocrine therapies are effective for the treatment of patients with ER-positive breast tumors and tamoxifen is the most widely used endocrine anti-estrogen treatment. Interestingly, a number of studies has implicated HuR in ER and HER2 expression regulation and tamoxifen resistance, suggesting that HuR may play a crucial role in breast cancer development and possibly treatment, as recently reviewed by our group [15].…”
Section: Introductionmentioning
confidence: 72%
See 4 more Smart Citations
“…ER-targeted endocrine therapies are effective for the treatment of patients with ER-positive breast tumors and tamoxifen is the most widely used endocrine anti-estrogen treatment. Interestingly, a number of studies has implicated HuR in ER and HER2 expression regulation and tamoxifen resistance, suggesting that HuR may play a crucial role in breast cancer development and possibly treatment, as recently reviewed by our group [15].…”
Section: Introductionmentioning
confidence: 72%
“…A gradually increasing number of studies have currently documented that HuR overexpression and cytoplasmic localization are associated with crucial clinicopathological parameters for patients' management and prognosis in several types of human malignancy, as recently reviewed by our group [15]. Moreover, a number of clinical studies in breast cancer patients have demonstrated that elevated HuR expression was correlated with crucial clinicopathological parameters and patients' survival, indicating that high HuR expression levels may constitute an aggravating factor for tumor growth and metastasis [15].…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations